Brewer’s Spent Grains as Alternative Ligno-Cellulosic Filler for the Preparation of Bio-Based Polymer Composites - Stefano De Luca; Kerstin Mueller; Lorenzo Tomei; Duccio Gallichi Nottiani; Daniel Milanese; Corrado Sciancalepore (Advances in Polymer Technology)
Brewer’s spent grains (BSGs) are lignocellulosic sources that can be considered promising economic alternatives to wood as biofillers to produce wood–plastic composites (WPCs). Given the high protein content (25 wt.%) of BSGs, alkaline hydrolytic solid–liquid (S/L) extractions were carried out at different pHs, with the goal of extracting as much protein as possible without altering or compromising the quality of the lignocellulosic matrix. Biocomposites with 10–50 wt.% biofiller were produced by blending polybutylene succinate (PBS) and poly(hydroxybutyrate-co-hydroxyhexanoate) (PHBH) with native BSG (BSG), BSG treated at pH 10.5 (BSG-S2_T2) and BSG treated at pH 12 (BSG-S2_T3). The injection-molded compounds were characterized in terms of structural, rheological, mechanical, morphological, and thermal properties to investigate the potential impact of different biofillers on the overall compatibility of the two different biopolymer matrices as an alternative to conventional wood flour-based WPCs. Fourier transform infrared (FT-IR) spectra, thermal (differential scanning calorimetry [DSC]), and morphological (scanning electron microscope [SEM]) analyses revealed only minor interactions. The melt flow rate (MFR) analyses showed the increased viscosity in PBS-based biocomposites when the filler concentration increased. In contrast, for PHBH-based composites, an increase in MFR values was obtained under the same test conditions, with a maximum peak of 97% for S2_T3 30 wt.% filler. From a mechanical point of view, the addition of reinforcing fibers led to a more significant increase in Young’s modulus (E) in PBS-based composites as the biofiller content increased, up to 98%, compared to pure PBS. On the contrary, in PHBH-based composites, the addition of fillers led to a significantly lower increase, with values between 14% and 20% compared to pure PHBH. The tensile strength (σB) and elongation at break (εB) decreased proportionally in the two biopolymer matrices as the percentage of natural filler increased, with properties similar to traditional WPCs. These results are consistent with the literature and support the application of PBS and PHBH biocomposites filled with BSG as an environmentally friendly alternative to conventional plastics.